King Henry VI, Part 1 - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"King Henry VI, Part 1" by William Shakespeare is a history play believed to have been written in 1591. Following the sudden death of the mighty Henry V, England's French territories crumble under rebellion while nobles squabble over power at home. As the young, uncrowned Henry VI inherits a fracturing kingdom, military disasters mount abroad and political factions$1 (Bsymbolized by red and white roses$1 (Bemerge at court. The legendary warrior Talbot battles French forces led by Joan of Arc, while personal jealousies among English lords set the stage for the Wars of the Roses. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Henry_VI,_Part_1
Release date is 1998-10-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: Henry VI, King of England, 1421-1471 -- Drama; Great Britain -- Kings and rulers -- Drama; Historical drama; Great Britain -- History -- Henry VI, 1422-1461 -- Drama